DẪN LIỆU VỀ HỌ ỐC GAI (GASTROPODA: MURICIDAE) TẠI KHU VỰC HUYỆN ĐẢO CÔ TÔ, TỈNH QUẢNG NINH - Nguyễn, Tài Tú; Hoàng, Thị Thuỳ Dương; Đỗ, Đức Sáng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DATA ON FAMILY MURICIDAE Rafinesque, 1815 (GASTROPODA: MURICOIDEA) IN CO TO ISLANDS, QUANG NINH PROVINCE Muricidae specimens were collected in three field trips from December, 2019 to June, 2021 in Co To Islands, Quang Ninh Province. In total, 22 species of Muricidae were collected, in which 18 species were identified to species, 4 species were identified to genera. Compared with the results of previous studies in Vietnam, our research has recorded 02 new species for Vietnam (E. junionae, L. lutescena), 07 new species recorded for the Gulf of Tonkin and 13 new species recorded for Co To Islands. Results of research bring the total number of species of the Muricidae in Vietnam to 185 species, bring the total number of species of the Muricidae in Co To Islands to 34 species. D. margariticola, E. contracta, I. sacellum, M. echinata species have a wide distribution in Co To Islands. These species are abundant and dominant at the subtidal. Meanwhile, there are 8 species with narrow distribution, only found in one island. These species are rarely encountered. The results showed that: Muricidae distributes mainly in the subtidal zone and habitat in hard bottoms. Data on the species composition and distribution of Muricidae is the scientific basis for the conservation and effective exploitation of mollusk resources in Co To islands.